Penerapan Persamaan Simultan pada Analisis Hubungan Ketersediaan dan Konsumsi Beras Untuk Melihat Kondisi Ketahanan Pangan - Ramadhan, Nashif Satria; Himalaya, Karina; Wardani, Aulia Pramudya; Maheswara, Aronad Brilliantino Evan; Khairunnisa, Evita; Budiasih, Budiasih (Politeknik Statistika STIS, 2023)
Rapid increase in population is a big challenge, especially for food security. As a staple food, rice has a vital role in the daily life of Indonesian people. This study aims to analyze the factors that influence availability and consumption of rice in 34 Indonesian provinces in 2021 using simultaneous equation estimated by Two Stage Least Square (2SLS). The results is rice availability and rice consumption had a positive and significant effect on each other. Harvested area also has a positive and significant effect on the rice availability, while price of rice has no significant effect. Furthermore, population has a positive and significant effect on rice consumption, while GRDP has no significant effect. Simulations were also carried out on the impact of decreased harvested area, population growth, and increase in GRDP on the availability and consumption of rice. If these conditions occur, rice availability cannot meet national rice consumption needs.